Navigated Transcranial Magnetic Stimulation in Neurosurgery - M. Krieg, Sandro (Springer International Publishing : Imprint: Springer, 2017)
This book is the first comprehensive work summarizing the advances that have been made in the neurosurgical use of navigated transcranial magnetic stimulation (nTMS) over the past ten years. Having increasingly gained acceptance as a presurgical mapping modality in neurosurgery, today it is widely used for preoperative mapping of cortical motor and language function, risk stratification and improving the accuracy of subcortical fiber bundle visualization. This unique work will provide neurosurgeons and neuroscientists who are starting their nTMS program essential and detailed information on the technique and protocols, as well as the current clinical evidence on and limitations of the various applications of nTMS. At the same time, more experienced nTMS users looking for deeper insights into nTMS mapping and treatment in neurosurgery will find clearly structured, accessible information. The book was prepared by an international mix of authors, each of which was chosen for their status as a respected expert on the respective subtopic, as evinced by their landmark publications on nTMS.
Keywords: Medicine.; Neurosciences.; Neuroradiology.; Neurology.; Neurosurgery.; Neuropsychology.; elektronické knihy; electronic books